GENEALOGI WACANA PADA PESAN AGITATIF PIDATO PRABOWO SUBIYANTO TENTANG NKRI BUBAR TAHUN 2030 - Cosmas Gatot Haryono (Bricolage : Jurnal Magister Ilmu Komunikasi, 2019)
ABSTRACTThe 2019 presidential election (Pilpres) is a very hot political battle compared to the 2014 election. The temperature of national politics has begun to heat up starting several months before the official campaign period set by the KPU. The "open battle" between the Jowoki camp and Prabowo's camp grew stronger through criticism, criticism, and even physical insult to Jokowi who was the incumbent president. One interesting issue of the various polemics that adorn the world of national politics ahead of the 2019 presidential election is the issue of the dissolution of NKRI in 2030. Prabowo states that in 2030 Indonesia is predicted to disband because of the behavior of national political elites who are far from caring for the small people. Apart from weak references, the issue of the dissolution of the NKRI has been a discourse in our national politics in the past few weeks. In this case, Prabowo has succeeded in constructing subjective reality in the social reality of society for the benefit of himself. Through the power he had, Prabowo instilled an understanding of pessimism in the mindsof the public that the state could fail and that the existing government also had the opportunity to fail, it needed to be replaced immediately. In the context of discourse fighting, even though it failed substantially, the speech was quite deceptive and horrendous. Despite experiencing an anti-climax, actually what was revealed by Prabowo was actually enough to help the community to identify some concerns or fears that the interests of many people (Indonesia) would be ruled out by the government. This research is a qualitative research with Faucoult's genealogy discourse method.Keywords; Political Communication, Pessimism, Agitation, Genealogy DiscourseABSTRAKPemilihan presiden (Pilpres) 2019 merupakan pertarungan politik yang sangat panas dibandingkan pemilu 2014. Suhu politik nasional mulai panas sudah dimulai sejak beberapa bulan menjelang masa kampanye resmi yang ditetapkan KPU. “Pertarungan terbuka” antara kubu Jowoki dan kubu Prabowo kian kencangmelalui kritikan, kecaman, bahkan hinaan secara fisik terhadap Jokowi yang adalah presiden petahana. Salah satu isu yang menarik dari berbagai polemik yang menghiasi dunia politik nasional menjelang pilpres 2019 ini adalah isu bubarnya NKRI di tahun 2030. Prabowo menyatakan bahwa tahun 2030 Indonesia diprediksikan akan bubar karena perilaku para elit politik nasional yang jauh dari kepedulian terhadap rakyat kecil. Lepas dari referensi yang lemah, isu bubarnya NKRI telah menjadi wacana dalam politik nasional kita beberapa minggu terakhir. Dalam hal ini, Prabowo telah berhasil mengkonstrukikan realitas subyektif dalam realitas sosial masyarakat untuk kepentingan dirinya. Melalui power yang dimiliknya, Prabowo menanamkan pemahaman pesimisme dalam benak masyarakat bahwa negara bisa saja gagal dan pemerintahan yang ada sekarang pun berpeluang juga untuk gagal, maka perlu diganti segera. Dalam konteks pertarungan wacana, meskipun gagalsecara substansi, pidato tersebut cukup mengecoh dan menghebohkan. Meskipun mengalami anti klimaks, sebenarnya apa yang diungkap Prabowo sebetulnya cukup membantu masyarakat untuk mengidentifikasi tentang adanya beberapa kekhawatiran atau ketakutan bahwa kepentingan masyarakat banyak (Indonesia) akan dikesampingkan oleh pemerintah. Penelitian ini merupakan penelitian kualitatif dengan metode genealogi wacana Faucoult.Kata Kunci; Komunikasi Politik, Pesimisme, Agitasi, Genealogi Wacana